Social and cultural transformations meaning of hemeronimes (on the example of the Tiflis-Armenian periodicals). - Danielyan, Taron; Harutyunyan, Hasmik; Santoyan, Aren (Bulletin of Yerevan University B: Philology, 2021)
Investigating the semantic transformations of the names of the organs of the Armenian periodical press in Tiflis, the authors note that the stages of semantization and desemantization of hemeronyms are influenced by certain social and cultural processes. The semantic transformations of hemeronyms are due to the functionality of the editions, which changes in certain chronotopic coordinates. The semantics of hemeronyms can undergo transformation both in expressive and in content terms. At different stages of use, hemeronyms may have the following semantic meanings: nominating stage - hemeronyms are expressed as ideonyms; legislative and legal stage - hemeronyms are used as ergonyms and pragmatonyms; market-competitive stage - hemeronyms function in the role of ergonyms, pragmatonyms, socionyms, pseudonyms, biblionyms; historical stage - hemeronyms function as documentonyms and chrematonyms. At the last stage, it is possible to revive hemeronyms as the name of a new media product with a historical allusion to a well-known publication of past years.
Keywords: ideonym; pragmatonym; pseudonym; socionym; ergonym